2020
DOI: 10.1093/jee/toaa240
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown ofcalreticulin, laccase, andSnf7Genes Through RNAi Is Not Effective to Control the Asian Citrus Psyllid (Hemiptera: Livideae)

Abstract: The Asian citrus psyllid, Diaphorina citri Kuwayama, transmits the bacteria Candidatus Liberibacter associated with huanglongbing (HLB), a devastating disease of the citrus industry. The use of genetically modified plants is an alternative to control this vector. Conversely, technology based on RNA interference (RNAi) for silencing specific genes of a target insect could be attempted. This work evaluated the knockdown effect of the target genes calreticulin (DcCRT), laccase (DcLAC), and Snf7 (DcSnf7) by RNAi t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 61 publications
1
8
0
1
Order By: Relevance
“…The Snf7 and CHC genes are involved in endocytosis, and endocytosis and lysosome pathways, respectively. All three genes are conserved across insect orders and have been evaluated in RNAi research for multiple insect species ( Baum et al, 2007 ; Angelotti-Mendonça et al, 2020 ), making them amenable for comparative analysis of RNAi characteristics with other better-studied insects. Further, optimal RNAi efficacy for biopesticide development rests on the consistent expression of the genes across all insect developmental stages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Snf7 and CHC genes are involved in endocytosis, and endocytosis and lysosome pathways, respectively. All three genes are conserved across insect orders and have been evaluated in RNAi research for multiple insect species ( Baum et al, 2007 ; Angelotti-Mendonça et al, 2020 ), making them amenable for comparative analysis of RNAi characteristics with other better-studied insects. Further, optimal RNAi efficacy for biopesticide development rests on the consistent expression of the genes across all insect developmental stages.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the aim was to avoid gene targets for which relative knockdown was less than 40%, to maximize the likelihood that results were reflective of psyllid responsiveness to each increase in dsRNA concentration in the series, for example, 1 ng/μl to 10 ng/μl, and yield a measurable knockdown phenotype for each. Further, the three genes selected are well-known RNAi targets in insects ( Baum et al, 2007 ; Baum and Roberts, 2014 ; Ulrich et al, 2015 ; Pereira et al, 2019 ; Angelotti-Mendonça et al, 2020 ), and are expressed constitutively in most organisms including insects ( Royle, 2006 ; Forgac, 2007 ; Weiss et al, 2009 ; Pinheiro et al, 2018 ). Finally, expression of each gene has been confirmed by scanning our laboratory transcriptome libraries constructed from PoP adult and nymphal stages, and in the PoP gut and salivary glands of both CLso-infected and -uninfected PoP (data not shown).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, knockdown of the arginine kinase and superoxide dismutase genes through feeding and iPS reduced the ACP adult survival rate [26]. In some other studies, despite successful gene silencing using iPS, however, dsRNA delivery through this method did not affect the insect survival rate or the expression of pterin-4-α-carbinolamine dehydratase, tomosyn, vitellogenin [26], laccase-1S, calreticulin, and Snf7 [57]. These contrasting results suggest that the RNAi-mediated ACP control also depends on target selection.…”
Section: Acp Control Using Rnai Technologymentioning
confidence: 92%
“…This delivery method involves the use of a detached leaf that absorbs a solution containing the dsRNA for gene silencing in insects via the petiole. Although this method with a Cy3-labeled dsRNA has been successfully used by Taning et al and Galdeano et al [26,55], Angelotti-Mendonça et al [57] demonstrated that most of the dsRNA absorbed by the detached leaves remained in the xylem. Because ACP mainly feeds on sap in the phloem and only derives water from the xylem, the insects likely ingested only a small amount of dsRNA from the xylem.…”
Section: Dsrna Deliverymentioning
confidence: 99%
“…. Em bioensaios com folhas destacadas após a absorção de uma solução aquosa com dsRNA foi obtido mortalidade e redução de transcritos em Diaphorina citri, inseto sugador de seiva do floema(ANGELOTTI-MENDONÇA et al, 2020). A seiva do floema é um meio livre de RNase ou com quantidade muito baixa, beneficiando a estabilidade do dsRNA(DOERING-SAAD et al, 2002).…”
unclassified